The Immersion Corrosion Resistance of Shot Peening and MAO Applied on AZ31−0.5% La Sheets - Elmansouri, G.; Kara, I. H.; Ahlatci, H.; Turen, Y. (Engineering, Technology & Applied Science Research, 2020)
In this study, the effect of Shot Peening (SP) and Micro Arc Oxidation (MAO) process on the corrosion resistance of 0.5% La with added AZ31 Mg alloy, hot rolled at different rolling speeds, was investigated. It was found that the surface of the rolled material at a rolling speed of 4.7m/min had higher surface smoothness values than the one rolled at 10m/min. It was observed that the corrosion rate changed in the first 40 of 168 hours. In the following hours, the corrosion rate showed different results according to the initial microstructure properties of the base materials. Initially, pore size was the dominant factor determining corrosion resistance, although, after coating, the corrosion rate was affected by the twins formed, based on rolling speed, which enhanced the corrosion rate between 48 and 168 hours.